Multiphoton dissociation of HeH+ below the He+(1s)+H(1s) threshold - Ursrey, D.; Anis, F.; Esry, B. D. (My University, 2012)
We discuss the strong-field dynamics of HeH+, the simplest stable heteronuclear molecule, focusing on identifying a laser regime for which there is a sufficient dissociation signal for experimental measurement. We numerically solve the time-dependent Schrödinger equation to obtain total dissociation probabilities, kinetic-energy release spectra, and momentum distributions for wavelengths from 800 to 2400 nm. The suitability of this simple system as a prototype for understanding the strong-field nuclear dynamics of heteronuclear dissociation is discussed.